2018
DOI: 10.1021/jacs.8b02089
|View full text |Cite
|
Sign up to set email alerts
|

Acid-Resistant Mesoporous Metal–Organic Framework toward Oral Insulin Delivery: Protein Encapsulation, Protection, and Release

Abstract: Diabetes affects millions of people worldwide and the number of diagnoses continues to climb annually. Though several effective medications and therapeutic methods have been developed to treat type 1 (T1DM) and type 2 (T2DM) diabetes mellitus, direct insulin injection remains the only effective treatment for insulin resistant (IR) diabetes patients. Here, we immobilize insulin in a crystalline mesoporous metal-organic framework (MOF), NU-1000, and obtain a high loading of ∼40 wt % in only 30 min. The acid-stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
268
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 366 publications
(280 citation statements)
references
References 39 publications
(49 reference statements)
7
268
0
5
Order By: Relevance
“…Metal–organic frameworks (MOFs), a class of tunable materials comprised of organic linkers and inorganic nodes, have been used as porous supports to enhance the stability and, in some cases, catalytic activity of the encapsulated enzymes . In particular, zirconium‐based MOFs (the NU‐10xx series) demonstrate excellent stability at a wide range of acidic and basic pH . The hierarchical pore structure allows for the inclusion of large catalytic guest molecules, while allowing substrate diffusion through an auxiliary channel and access to the catalyst through apertures connecting the channels (Scheme a).…”
Section: Methodsmentioning
confidence: 99%
“…Metal–organic frameworks (MOFs), a class of tunable materials comprised of organic linkers and inorganic nodes, have been used as porous supports to enhance the stability and, in some cases, catalytic activity of the encapsulated enzymes . In particular, zirconium‐based MOFs (the NU‐10xx series) demonstrate excellent stability at a wide range of acidic and basic pH . The hierarchical pore structure allows for the inclusion of large catalytic guest molecules, while allowing substrate diffusion through an auxiliary channel and access to the catalyst through apertures connecting the channels (Scheme a).…”
Section: Methodsmentioning
confidence: 99%
“…The study found that the proper tailoring of pore size and surface charge was critical for ensuring favorable interactions with protein (e.g., insulin) which in turn, will determine the loading amount of protein. The 1D pores of NU‐1000 allowed insulin molecule to diffuse through the framework but pepsin was excluded while being transported by the bloodstream due to the size mismatch ( Figure ) …”
Section: Mof Proteinsmentioning
confidence: 99%
“…Insulin remains folded while insulin@NU‐1000 can withstand exposure to stomach acid/digestive enzyme, with the release of pepsin and insulin occurring in the PBS solution (bloodstream). Reproduced with permission . Copyright 2018, American Chemical Society.…”
Section: Mof Proteinsmentioning
confidence: 99%
“…[10,11] Fore xample,M OFs have been demonstrated to be excellent candidates for micro/ nanomedicine-extended or controlled cargo delivery. [12][13][14][15][16] In these delivery models,M OFs with long-term chemical stability in media serve as drug release regulators upon activation by diverse stimuli such as media pH, temperature or pressure. [10] MOFs using as low drug release model are beneficial for moderate to high solubility compounds and may improve chemical stability [12][13][14][15] of molecules by limiting total exposure of the compound in the digestive tract.…”
mentioning
confidence: 99%